Analisis Kritis Asesmen Diagnostik untuk Menentukan Gaya Belajar dalam Pembelajaran Berdiferensiasi - Putri, Candra Avista; Basith, Abdul; Firdhausyah, Ananda Ammathul; Syaifuddin, Ahmad (CV. Gerasi Insan Nusantara, 2023)
ABSTRACT: Differentiated learning is an approach that recognizes the differences between each student and another student who has their abilities, readiness, interests, and learning styles. So that there is a need for diagnostic assessment analysis which is used to make it easier to determine and map students according to their respective abilities. The method in this research is to use literature studies and obtain data from forum group discussion. The result of this study is that diagnostic assessment can be carried out by conducting tests of student learning readiness, interests, and learning styles and can be done with multiple intilegent research strategies.